Optical studies of GaN nanocolumns containing InGaN quantum disks and the effect of strain relaxation on the carrier distribution - Holmes, M; Park, Y; Wang, X; Chan, C; Reid, B; Kim, H; Luo, J; Warner, J; Taylor, R (2012)
The optical properties of GaN nanocolumns containing pairs of In xGa 1-xN (x ∼ 0.1) quantum disks (QDisks) have been experimentally measured. Strain simulations reveal an inhomogeneous distribution of strain, and furthermore, a relaxation between successive QDisks along the growth direction of the column. Although this inhomogeneous distribution of strain may indicate a lateral separation of carriers in the QDisk, the decay lifetime of the emission suggests far less carrier separation. The quantum confined stark effect is found to create an inhomogeneous distribution of charge within the QDisks along the growth direction of the rod. © 2012 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.